Overview of the initial growth phase in the number of cases and deaths caused by COVID-19 in Brazil (Research, Society and Development, 2020)
A continuous outbreak of pneumonia associated with a new coronavirus (COVID-19) was reported in the city of Wuhan in China and quickly spread to many countries, including Brazil. As it is a very contagious disease and rapidly worsening the patient's clinical condition, understanding how cases and deaths developed in the first days can help in planning governmental measures, even for possible future pandemics. Thus, the objective of this work is to present how the number of infected people grew in the first sixty days and confirmed deaths in the initial forty days from the first record, caused by COVID-19 in Brazil. Nonlinear regression models were adjusted, with data are taken from the Ministry of Health's Coronavirus Panel, to statistically model how the data behaves in the aforementioned period, and maps describing how COVID-19 evolved in Brazilian states were presented, until the end of April of 2020. The results showed that the models used (Gompertz and Logistics) were adequate to explain the development of the number of cases and deaths from the disease in its initial phase, and in this period studied, the epidemic had not yet reached its peak, when there is a greater number of cases and deaths, and it is still possible to estimate the growth rate. The map proved to be adequate to verify how the cases and deaths in the states grew in relation to the period under study.